Rationale for Involved Field Stereotactic Body Radiation Therapy-Enhanced Intermittent Androgen Deprivation Therapy in Hormone-Sensitive Nodal Oligo-Recurrent Prostate Cancer Following Prostate Stereotactic Body Radiation Therapy - Carrasquilla, Michael; Creswell, Michael L.; Pepin, Abigail N.; Wang, Edina; Forsthoefel, Matthew; McGunigal, Mary; Bullock, Elizabeth; Lei, Siyuan; Collins, Brian T.; Lischalk, Jonathan W.; Esposito, Giuseppe; Aghdam, Nima; et al. (Frontiers in Oncology, 2021)
Lymph node recurrent prostate cancer is a common clinical scenario that is likely to increase significantly with the widespread adoption of novel positron emission tomography (PET) agents. Despite increasing evidence that localized therapy is disease modifying, most men with lymph node recurrent prostate cancer receive only systemic therapy with androgen deprivation therapy (ADT). For men who receive localized therapy the intent is often to delay receipt of systemic therapy. Little evidence exists on the optimal combination of local and systemic therapy in this patient population. In this hypothesis generating review we will outline the rationale and propose a framework for combining involved field SBRT with risk adapted intermittent ADT for hormone sensitive nodal recurrent prostate cancer. In patients with a limited number of nodal metastases, involved field stereotactic body radiation therapy (SBRT) may have a role in eliminating castrate-resistant clones and possibly prolonging the response to intermittent ADT. We hypothesize that in a small percentage of patients, such a treatment approach may lead to long term remission or cure.